2023
DOI: 10.3390/v15010168
|View full text |Cite
|
Sign up to set email alerts
|

ERVWE1 Reduces Hippocampal Neuron Density and Impairs Dendritic Spine Morphology through Inhibiting Wnt/JNK Non-Canonical Pathway via miR-141-3p in Schizophrenia

Abstract: Human endogenous retroviruses (HERVs) are remnants of ancestral germline infections by exogenous retroviruses. Human endogenous retroviruses W family envelope gene (HERV-W env, also called ERVWE1), located on chromosome 7q21-22, encodes an envelope glycoprotein from the HERV-W family. Mounting evidence suggests that aberrant expression of ERVWE1 involves the etiology of schizophrenia. Moreover, the genetic and morphological studies indicate that dendritic spine deficits may contribute to the onset of schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…ELISA of blood samples revealed higher ERVW-1 levels in schizophrenia patients ( Fig. 2 D), consistent with our previous study ( Huang et al., 2011 ; Li et al., 2023 ; Wang et al., 2018 ; Wu et al., 2023 ; Xia et al., 2021 ; Yan et al., 2022 ; Yao et al., 2023 ). Furthermore, Spearman's analysis showed that ERVW-1 negatively correlated with GPX4 ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…ELISA of blood samples revealed higher ERVW-1 levels in schizophrenia patients ( Fig. 2 D), consistent with our previous study ( Huang et al., 2011 ; Li et al., 2023 ; Wang et al., 2018 ; Wu et al., 2023 ; Xia et al., 2021 ; Yan et al., 2022 ; Yao et al., 2023 ). Furthermore, Spearman's analysis showed that ERVW-1 negatively correlated with GPX4 ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…HERVs contribute to development of various disorders through multiple mechanisms ( Geis et al., 2020 ; Zhang et al., 2022 ), such as assembling viral particles ( Wang et al., 2018 ), generating HERV-derived lncRNAs ( Zhou et al., 2019 ) and dsRNAs ( Canadas et al., 2018 ), acting as promoters or enhancers to regulate cellular gene expression through LTR cis -regulatory element ( Yu et al., 2013 ), or encoding viral proteins to regulate host cell signaling networks ( Li et al., 2023 ; Wang et al., 2018 ; Wu et al., 2023 ; Xia et al., 2021 ; Yan et al., 2022 ; Yao et al., 2023 ). Abnormal expression of ERVW-1 has been linked to schizophrenia ( Huang et al., 2011 ; Xia et al., 2021 ; Yan et al., 2022 ), and further studies have shown that ERVW-1 induces inflammatory abnormalities, including promoting NO release ( Xiao et al., 2017 ), activating TLR3 signaling pathway ( Wang et al., 2018 , 2021 ), promoting cytotoxic T lymphocyte (CTL) responses of glial cells ( Tu et al., 2017 ), and inducing innate immune activation by upregulating IFN-β, thereby mediating neuronal apoptosis ( Li et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the first treatment targeting a human endogenous retrovirus (HERV) protein enters into phase III clinical trials to combat multiple sclerosis (MS) progression [ 1 ], HERVs are becoming increasingly promising targets in cancer diagnostics and therapies. Previously, HERVs have been identified as involved in the progression of complex diseases such as MS [ 1 , 2 ], schizophrenia [ 3 , 4 ], and type 1 diabetes [ 5 , 6 ]. Lessons learned from these phenotypes have illuminated the potential for HERVs to impact human cancer development and treatment options.…”
Section: Introductionmentioning
confidence: 99%